Physical activity as an effort to prevent hypertension in the elderly - Zusana A. Sasarari; Sumarmi Sumarmi; Yoga Tri Wijayanti; A.Syamsinar Asmi (Edukasi Ilmiah Indonesia, 2024)
Introduction hypertension is one of the common health problems in the elderly population and can increase the risk of cardiovascular disease and other complications. Physical activity has been shown to be effective in preventing and managing hypertension in the elderly. Objective identify and evaluate different types of physical activity that can help in the prevention of hypertension in the elderly. Methods type of quantitative research with a case control approach. The total population is 42 respondents. Data collection using questionnaires. Data analysis using Chi-square test. Results that physical activity can prevent hypertension in the elderly chi-Square test results with p value: 0.634. which means that physical activity is not a risk factor for causing hypertension. Conclusion regular and diverse physical activity is an important strategy in the prevention of hypertension in the elderly. Physical activity programs tailored to individual needs and abilities should be encouraged and widely implemented in an effort to maintain heart health and reduce the risk of hypertension in the elderly population. Further efforts are needed to increase public awareness of the importance of physical activity in maintaining heart health and preventing cardiovascular disease in the elderly